Review of safety and reliability insights for sheet pile wall design (2025)
This paper presents a review of the limit state design of sheet pile walls. The principles of soil arching, static and kinematic compatibility, partial factor approach, load and resistance factor design (LRFD) approach, and typical and characteristic design values are explored from a diachronic perspective of code development. A reliability-based design framework is implemented to test the performance of the sheet pile design principles from four design cases involving key geohydraulic conditions and ultimate limit states. The results indicate that the CSA-S6-19 and AASHTO LRFD BDS (2020) codes are not robust for sheet pile design involving high water loadings and multi-stratified ground profiles. The current LRFD calibration domain, the development bases of apparent earth pressures, and mean values of ground properties appear to be insufficient to achieve satisfactory performance compared to Eurocode 7 – Second Generation. On the other hand, Geoguide-1 (1982) exhibits an outstanding performance under high water loadings due to the magnitude of the mobilised strength parameters. The DS 415:1965 code leads to overly optimistic designs under Hansen's (1953) theory. However, it has promising potential to study the failure mechanisms of anchored and propped sheet pile walls with a low centre of rotation, situations that produce composite rupture zones, and for which modern North American and European codes do not provide guidelines.